THE EFFECT OF THINK PAIR SHARE METHOD ON STUDENTS WRITING RECOUNT TEXT ABILITY OF THE TENTH YEAR STUDENTS OF SMA DHARMA PATRA PANGKALAN BRANDAN - Nudia Yultisa; Juliansyah; Winda Amalia; Eka Rahmadanta Sitepu (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
The objective of this study is to find out there is a significant effect using think pair share method on students writing recount text ability of the tenth year students of SMA Dharmapatra Pangkalan Brandan. This study was an experimental research. This study used a system of control class and experimental class, which acts as a control class benchmark basic ability students in writing recount text without application of the method, while the experimental class was given a Think Pair Share method with the sample of the study was put into two groups, that were 24 students as control class and 24 students as experimental class. Students writing recount text in control class have been found the averages result of an essay test is 54,58. It mean that the ability students in writing recount text was needed more effective learning method of lesson writing recount text. Students writing recount text in experimental class have been found the averages result of an essay test is 84,37. It mean that the ability students in writing recount text has increased after the students gave the aplication of think pair share method. After knowing the homogeneity of the data by used statistics test then have been found the data was homogeneous, then the researcher used t formula to determine of hypothesis test. Based on the calculation above, it has been known tcount is 6,6733. To test the hypothesis based on data that has been obtained, then in accordance with the provisions that have been established that the hypothesis accepted if tcount > ttable. It has been known the ttable is 1,6786, then 6,6733 > 1, 6786. It concluded the hypothesis was accepted, it concluded that using Think Pair Share method significantly affect students’ writing recount text ability of the tenth year students of SMA Dharma Patra Pangkalan Brandan.